2020
DOI: 10.12659/msm.928919
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Type X Alpha 1 (COL10A1) Contributes to Cell Proliferation, Migration, and Invasion by Targeting Prolyl 4-Hydroxylase Beta Polypeptide (P4HB) in Breast Cancer

Abstract: Background Breast cancer, a common malignant tumor, has been considered as the leading cause of cancer-related death in women. Collagen type X alpha 1 (COL10A1) is overexpressed in breast cancer. The current study was designed to determine the functional involvement and regulatory mechanism of COL10A1 on the growth and metastasis of breast cancer. Material/Methods COL10A1 and Prolyl 4-hydroxylase beta polypeptide (P4HB) expressions in normal tissues and tumor tissues of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…These findings indicate that P4HB may serve as a potential molecular marker for the diagnosis and treatment of cancer. We demonstrated that low serum P4HB level is significantly associated with better DFS and OS, which is consistent with the findings reported by Yang et al [ 105 ]. The study demonstrated that downregulation of P4HB represses the promoting effects of overexpressed COL10A1 on the proliferation, migration, and invasion of BC cells and, conversely, upregulation of P4HB promotes BC cell proliferation and clone-forming ability, as well as increasing BC cell migration and invasion [ 105 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings indicate that P4HB may serve as a potential molecular marker for the diagnosis and treatment of cancer. We demonstrated that low serum P4HB level is significantly associated with better DFS and OS, which is consistent with the findings reported by Yang et al [ 105 ]. The study demonstrated that downregulation of P4HB represses the promoting effects of overexpressed COL10A1 on the proliferation, migration, and invasion of BC cells and, conversely, upregulation of P4HB promotes BC cell proliferation and clone-forming ability, as well as increasing BC cell migration and invasion [ 105 ].…”
Section: Discussionsupporting
confidence: 93%
“…COL4A2 knockdown can reduce triple‐negative breast cancer cells migration and proliferation, suggesting that COL4A2 may be a target for the treatment of triple‐negative breast cancer 65 . In addition, the interaction between COL10A1 and prolyl 4‐hydroxylase possibly regulates the proliferation, migration and invasion of breast cancer cells 66 …”
Section: Network‐forming Collagens Regulate Tumor Invasion and Metast...mentioning
confidence: 99%
“…On the other hand, PPIB, a peptidylpropyl isomerase, participated in colorectal cancer progression and chemoresistance [49]. Studies have also suggested that P4HB may extensively regulate tumor progression and prognosis of patients with cancer [50][51][52][53][54], including BRCA [55,56]. In BRCA, TMED9 may affect cancer progression and prognosis by interacting with these proteins.…”
Section: Discussionmentioning
confidence: 99%